2018
DOI: 10.1128/jb.00006-18
|View full text |Cite
|
Sign up to set email alerts
|

CpxR-Dependent Thermoregulation of Serratia marcescens PrtA Metalloprotease Expression and Its Contribution to Bacterial Biofilm Formation

Abstract: PrtA is the major secreted metalloprotease of Previous reports implicate PrtA in the pathogenic capacity of this bacterium. PrtA is also clinically used as a potent analgesic and anti-inflammatory drug, and its catalytic properties attract industrial interest. Comparatively, there is scarce knowledge about the mechanisms that physiologically govern PrtA expression in In this work, we demonstrate that PrtA production is derepressed when the bacterial growth temperature decreases from 37°C to 30°C. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…In contrast, E. coli CpxR-P can directly bind to the fimA promoter, thus negatively affecting the production of type 1 fimbriae and biofilms (44). S. marcescens CpxR negatively regulates biofilm formation by directly inhibiting the expression of PrtA (31). For the first time, we found that the P. mirabilis CpxR-regulated zapABCD genes (encoding T1SS and ZapA protease) participate in biofilm formation, which corresponds with the role of CpxAR TCS in the regulation of virulence factors.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In contrast, E. coli CpxR-P can directly bind to the fimA promoter, thus negatively affecting the production of type 1 fimbriae and biofilms (44). S. marcescens CpxR negatively regulates biofilm formation by directly inhibiting the expression of PrtA (31). For the first time, we found that the P. mirabilis CpxR-regulated zapABCD genes (encoding T1SS and ZapA protease) participate in biofilm formation, which corresponds with the role of CpxAR TCS in the regulation of virulence factors.…”
Section: Discussionmentioning
confidence: 68%
“…4). Because we observed that ZapA expression was not associated with P. mirabilis autolysis (data not shown) as was shown to be the case for PrtA metalloprotease in S. marcescens (31), we can rule out the possibility that ZapA-dependent liberation of eDNA could act to modulate the formation or maintenance of P. mirabilis biofilms. Further studies are needed to reveal the scenarios of zapA involvement in the biofilm-forming process.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Liu et al obtained a super PG-producer S. marcescens jx1 which could produce 6.5 g/L of PG by microwave mutagenesis technology [11]. Furthermore, several reports have shown the influence of temperature on the phenotypes or enzymes of S. marcescens, such as the temperature-dependent resistance of S. marcescens to norfloxacin (hydrophilic fluoroquinolone) and nalidixic acid (hydrophobic quinolone) [12], its swimming or swarming motility [13,14], its outer membrane vesicles [15], and its metalloproteases and serine proteases [16,17].…”
Section: Introductionmentioning
confidence: 99%